+0  
 
0
72
1
avatar

Wieso ist (t^2)/((t^3)-1) = (1/3)*ln(t^3-1)

 13.09.2019
 #1
avatar+8564 
+1

Wieso ist (t^2)/((t^3)-1) = (1/3)*ln(t^3-1)

 

\(\frac{t^2}{t^3-1}=\frac{ln(t^3-1)}{3}\\ \frac{3\cdot t^2}{t^3-1}=ln(t^3-1)\)

 

\(Nur\ f\ddot ur\ {\color{blue}t=1,924626}\ ist\)

\(\frac{t^2}{t^3-1}\approx \frac{ln(t^3-1)}{3}\)

\(\frac{3\cdot t^2}{t^3-1}-ln(t^3-1)\approx 0\)

\(\frac{3\cdot t^2}{t^3-1}-ln(t^3-1)=15,84902\times 10^{-8}\)

laugh  !

 14.09.2019
bearbeitet von asinus  14.09.2019
bearbeitet von asinus  14.09.2019

11 Benutzer online

avatar